Provinsi Papua Sebelum dan Setelah 18 Tahun Pemberian Dana Otonomi Khusus - Rindang Mustikawati; Arief Maulana (Universitas Teuku Umar, 2020)
Papua Province is an area whose development is still lagging behind in Indonesia. The continually conflicts causes the development of the Province of Papua is very behind compared to other regions. To overcome this problem, the government provides special autonomy funds to make improvements in the fields of education, poverty, health, economic improvement and infrastructure. This study analyzes the differences in the fields of education, health and poverty before and after the granting of the Papua special autonomy fund. By analyzing these areas, we can see the effectiveness of the special autonomy fund after 18 years of funding by the central government. This study is a policy study (policy research) by collecting data and then analyzed into a conclusion and recommendation. The method used in this study is descriptive qualitative. Data collection techniques are done through literature study and Focus Group Discussion. The results of this study indicate that the conditions of education, health, and poverty alleviation before and after special autonomy did not change significantly. The change is very slow when compared to the large amount of special autonomy funds allocated each year. This is caused by the institutional system of government that has not worked effectively and efficiently as well as in the quality and quantity of existing human resources.